Factors influencing cyberbullying behavior among Malaysian tertiary students / Nor Azian Abdul Rahman ...[et al.] - Abdul Rahman, Nor Azian; Hussein, Norashikin; Rusdi, Syezreen Dalina; Abd Aziz, Zarith Delaila Abd Aziz (Faculty of Business and Management UiTM Shah Alam, 2020)
Cyberbully is an evolvement from traditional and physical bully to bullying through internet. The advancement of internet and social media has provided a new platform through which children, adolescents, and young adults to explore the virtual world and exposes them to be involved in cyberbully as a target or an aggressor. Past studies have demonstrated that cyberbullying behaviour has adverse physical and mental health consequences for individuals. However, study on cyberbully behaviour in the context of Malaysia is still limited. In fact, tertiary students remain an understudied population regarding cyberbullying. Thus, the aim of this study is to determine the relationship between netiquette, loneliness and emotional availability of parents and cyberbullying behaviour. Data was collected from tertiary students from a public university in Malaysia using survey questionnaires. Based on the findings, it was found that only netiquette was found to have negative significant relationship with cyberbullying behaviour. This study is significant to the Ministry Higher Education, institutions of higher learning education and community on identifying the factors and subsequently creating awareness programs in dealing with cyberbullying behaviours.